The modified urdu version of international prostate symptom score: A psychometric validation study - Salman, M.; Khan, A.; Sulaiman, S.; Hughes, Jeff; Khan, J.; Hussain, K. (2018)
© 2018 by Turkish Association of Urology. Objective: The objective of the current study was to develop an Urdu version of the International Prostate Symptom Score (IPSS-U) and validate it for Pakistani patients suffering from lower urinary tract symptoms (LUTS). Material and Methods: IPSS-U was developed by a two-step forward and back translation and to evaluate its psychometric properties, a prospective study involving patients suffering from LUTS (n=267) was conducted at Outpatient Urology Department, Mayo Hospital, Lahore, Pakistan. Internal consistency and reproducibility were assessed using Cronbach's alpha and the Intra-Class Correlation Coefficient (ICC). Moreover, exploratory, and confirmatory factor analyses were performed to determine dimensionality of IPSS-U items. Results: Overall reliability of IPSS-U was satisfactory (Cronbach’s alpha=0.72, ICC of symptom ques-tions=0.92 and ICC of QOL index=0.75). Exploratory factor analysis revealed that two factors were consistent, which together explained 59.8% of the variance. IPSS-U items 1, 3, 5 and 6 were components of the first factor whereas item 2, 4 and 7 were components of the second factor. All the items loaded high on their factors and there were no cross loadings. Moreover, confirmatory factor analysis also showed two-factor model, with acceptable fitting patterns. Conclusion: IPSS-U is a valid and reliable non-gender specific instrument to assess the frequency and severity of LUTS in Urdu-speaking population.